(untitled) (Indagatio Didactica, 2024)
This study aims to analyze children’s understanding of environmental preservation through playful activities in Early Childhood Education. Based on qualitative research carried out with children aged 4 and 5 years old at a public school in Belém do Pará, a sequence of playful activities was conducted with Science, Technology and Society (STS) approaches, involving scavenger hunts, board games and drawing. To construct the data, we opted for participant observation, written records and audio recordings of children’s interactions during the activities they experienced. As an analysis method, we used Discursive Textual Analysis. The results indicated that playing emerges as a powerful tool to encourage learning and debate about environmental issues, allowing children to express their opinions and begin to understand scientific concepts in a contextualized and adapted way. Furthermore, the study highlighted the importance of understanding children’s prior ideas and challenging them to go beyond what they already know, promoting a more meaningful education. It was also observed that children’s imagination influences children’s understanding of environmental issues, allowing them to attribute personal and social meanings to the concepts of environmental preservation and human responsibility. In short, the integration of playful activities with STS Education in Early Childhood Education is essential to stimulate reflections on environmental awareness in children, contributing to the formation of responsible subjects in the face of contemporary environmental challenges.